2017
DOI: 10.1177/0954409717702019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic performance of continuous railway bridges: Numerical analyses and field tests

Abstract: In this study, a refined finite element model was built that represented the structural and mechanical properties of railway bridges. A coupled vehicle-bridge vibration model was established to simulate the dynamic behavior of the bridge under moving trains. Field tests were then conducted to determine the free vibration characteristics as well as the strain, displacement, and acceleration of the bridge structure under trains moving at different speeds and braking at a specified position from a set speed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the wake of development in heavy-haul and high-speed railways over the world, the problems of train-bridge dynamic interaction have become increasingly prominent, and considerable progress has been made in this field over the recent decades. Most researchers used field tests and numerical simulations to investigate the vehicle-bridge dynamic interaction [4][5][6][7][8][9]. Numerical models such as moving load models [10,11] and dynamic interaction models [12][13][14][15][16][17][18] have been developed for the train-bridge system (TBS) dynamic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, fully prestressed concrete beams can be turned into partially prestressed concrete beams under the effects of overloading or other extreme events. Moreover, cracks are not allowed in fully prestressed concrete beams under service loads, which is different from partially prestressed concrete beams.Model tests and in situ tests have been considered as effective approaches to investigate mechanical performances of structures [22][23][24][25][26][27][28][29][30]. In this study, a full-scale fatigue test of a prestressed concrete beam was carried out.…”
mentioning
confidence: 99%
“…Model tests and in situ tests have been considered as effective approaches to investigate mechanical performances of structures [22][23][24][25][26][27][28][29][30]. In this study, a full-scale fatigue test of a prestressed concrete beam was carried out.…”
mentioning
confidence: 99%